Education and Assistance in Portugal: rhythms and evolution - Maria de Fátima Reis (Escola Superior de Educação de Paula Frassinetti, 2016)
Supposing that the assistance system of the constitutional monarchy was based either on the consolidation of the wide network of Misericórdias - non-ecclesiastical institutions, with their own financial resources, under the State's control - or in the existing hospital structure, of royal, noble or corporate initiative, in the Houses of foundling children and, although residual, in the brotherhoods and thirds religious orders, coming the associations of piety and beneficence to be obliged to subsidize the primary education of the parish, this study aims to understand as the mutual associations, the charitable associations, the individual charity and the new foundations - night shelters, nursing and elderly homes, nurseries and lactaries, supervised by the State -, occupied the care and the educational space resulting from the expulsion of the religious orders from Portugal. Thus, it's recognized the role played by these associations and by the individual practices when the Orders return. Keywords: Beneficence; Charity; Assistance; Teaching; Education